Neuroprotective and antioxidant effect of Curcuma longa (Rhizome) methanolic extract on SH-SY5Y cells and Javanese medaka - Hassan, Ibrahim Maina; Wan Ibrahim, Wan Norhamidah; Mohamat Yusuf, Ferdaus; Ahmad, Siti Aqlima; Ahmad, Syahida (Pakistan Journal of Pharmaceutical Sciences, 2021)
Diseases caused by oxidative stress can be prevented by antioxidant. Current treatments for those neurodegenerative diseases are not effective and cause many side effects. Thus, the search for alternative medicines is in high demand. Therefore, the main purposed of this study is to evaluate the neuroprotective effects of Curcuma longa (rhizome) 80% methanol extract. Antioxidant using dichlorofuoresence diacetate (DCF-DA) assay on SH-SY5Y cells revealed high activities of Curcuma longa (rhizome) extract with IC50 of 105.9±0.8 µg/mL. Sub-acute and chronic toxicity tests of the plant extract on adult Javanese medaka (Oryzias javanicus) showed high toxicity effect with LC50 of 24.15±0.8 mg/L and 13.69±0.7 mg/L respectively. Neuroprotective tests using cholinesterase assay disclose significant differences at P<0.05 between the group that are exposed to arsenic and treated with the crude extract and the group that are exposed to only arsenic. Identification of vitexin and isovitexin justified the high antioxidant potential of this plant leaf and it highest benefit to be used as medicinal supplement.